Development of a highly reproducible system to evaluate inhibition of cytochrome P450 3A4 activity by natural medicines - Yu Sato; Takamitsu Sasaki; Shogo Takahashi; Takeshi Kumagai; Kiyoshi Nagata (Journal of Pharmacy & Pharmaceutical Sciences, 2015)
PURPOSE: In recent years, a number of natural medicines have been reported to have inductive or inhibitive effects on the activity of drug metabolizing enzymes, upon co-administration with prescribed medicines. However, information regarding natural medicine-drug interactions that influence drug metabolism is limited owing to the lack of efficient screening method for such interactions. Therefore, to understand whether P450 activity is affected by natural medicine in small intestines, we have established frozen recombinant P450-expressing cells infected with human CYP3A4 expressing adenovirus (Ad-CYP3A4) to evaluate the effect of natural medicines on CYP3A4 activity. METHODS: Ad-CYP3A4 cells were created by infecting HepG2 cells with Ad-CYP3A4 at 10 multiplicity of infection (MOI) and these cells were stored using cryopreservation medium (fAd-CYP3A4 cells) to obtain long-term consistent data and stable supplies of cells expressing a constant level of CYP3A4 activity. RESULTS: The CYP3A4 activity in fAd-CYP3A4 cells remained unaffected at the end of each frozen period (0, 1, 2, and 6 months). Inhibitory effect on CYP3A4 activity by typical inhibitors (ketoconazole, hyperforin) and natural medicines (Cat’s Claw, Devil’s Claw, Feverfew, Peppermint Oil, Red Clover, and Siberian Eleuthero) were evaluated. The inhibitors had nearly equal IC50 values in fAd-CYP3A4 cells, Ad-CYP3A4 cells and recombinant CYP3A4 microsomes. Cat’s Claw, Peppermint Oil and Siberian Eleuthero inhibited CYP3A4 activity more potently than 0.1 μM ketoconazole in fAd-CYP3A4 cells. CONCLUSIONS: In the present study, we have successfully developed a highly reproducible system to evaluate CYP3A4 inhibition in small intestines by natural medicines.